IMPACT OF COMMERCIAL STRIPED CATFISH (PANGASIANODON HYPOPHTHALMUS) FARMING ON FARMERS’ LIVELIHOOD AND ENVIRONMENT IN BANGLADESH - Khaleda Nasrin; Yeamin Hossain (Science Journal of University of Zakho)
Striped catfish, Pangasianodon hypothalamus (Sauvage, 1878), has gained popularity among the Bangladeshi commercial fish farmers because of its rapid growth and high tolerance of adverse ecological conditions. The study aims to examine the impact of farmers’ socio-economic and farming features on their livelihood outcomes of Pangas (LOP), considering the sustainable livelihood approach (SLA) and the negative impacts of commercial farming activities on the surrounding environment using a mixed-method approach. A quantitative survey was conducted using a pre-tested structured questionnaire, and qualitative data were explored through focus group discussions (FGDs), in-depth interviews (IDIs), and key informant interviews (KIIs) to assess the impact. Data were computed using descriptive statistics, rank order, correlation coefficient, and regression analysis. In terms of LOP, the highest progress was observed in human capital (87.5%), followed by physical capital (75.7%), financial capital (70%), social capital (55.7%), and natural capital (38%). The farmers’ education, experience, knowledge of fish farming, and adoption of modern farming technology correlated positively, whereas age correlated negatively with the LOP and significantly impacted the achievement of the outcomes. Farming intervention was encouraged to establish various upward and backward linkage industries and create employment opportunities, which contributed to economic progress. On the other side, rapid expansion of pangas farming impacted the surrounding environment by converting two or more croplands (37%) into a closed pond and discharging polluted water (52%) and bottom sludge (49%) into natural water bodies. Raising dikes of fish ponds caused waterlogging in the crop field during cultivation, which also hampered the navigation of aquatic animals during the breeding season. Moreover, harmful chemical discharges were blamed for the decline of aquatic animals. Therefore, it is necessary to implement sustainable aquaculture practices along with proper monitoring and evaluation processes to ensure safe aqua-food production in an environmentally friendly manner, thereby achieving sustainable development goals.